2004
DOI: 10.1016/j.apcatb.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the selective catalytic reduction of NOx by C2H5OH over Ag/Al2O3

Abstract: [1] The exchange of carbonyl sulfide (COS) between lawn and the atmosphere was investigated by using a static enclosure under natural field conditions. The results indicated that the lawn acted as a sink for atmospheric COS and a source of dimethyl sulfide (DMS). The exchange fluxes of COS and DMS ranged between À3.24 pmol m À2 s À1 and À94.52 pmol m À2 s À1 , and between 0 and 3.14 pmol m À2 s À1 , respectively. The lawn was capable of continuously absorbing COS in nighttime as well as in daytime. The COS flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
169
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(180 citation statements)
references
References 49 publications
11
169
0
Order By: Relevance
“…Further studies confirmed that the enolic species originating from the partial oxidation of butyl alcohol (BA), sec-butyl alcohol (SBA), and isobutyl alcohol (IBA), propyl alcohol, 160 isopropyl alcohol (IPA), 161 and acetaldehyde 162 over Ag/Al 2 O 3 also exhibited high activity toward NO + O 2 , and thus are responsible for NO x reduction by these oxygenated hydrocarbons. The characteristic IR peaks of -NCO located around 2230 and 2250-2260 cm À1 have been commonly observed on Ag/Al 2 O 3 during HC-SCR, while the assignments of their coordination sites are still controversial.…”
Section: Reactivity Of Intermediates Originating From Partial Oxidatimentioning
confidence: 87%
See 1 more Smart Citation
“…Further studies confirmed that the enolic species originating from the partial oxidation of butyl alcohol (BA), sec-butyl alcohol (SBA), and isobutyl alcohol (IBA), propyl alcohol, 160 isopropyl alcohol (IPA), 161 and acetaldehyde 162 over Ag/Al 2 O 3 also exhibited high activity toward NO + O 2 , and thus are responsible for NO x reduction by these oxygenated hydrocarbons. The characteristic IR peaks of -NCO located around 2230 and 2250-2260 cm À1 have been commonly observed on Ag/Al 2 O 3 during HC-SCR, while the assignments of their coordination sites are still controversial.…”
Section: Reactivity Of Intermediates Originating From Partial Oxidatimentioning
confidence: 87%
“…162,165,166,173,179 Two kinds of surface enolic species, adsorbed only on Al sites (CH 2 QCH-CHQCH-O-Al 6 O 5 (OH) 8 ) and bound on or close to Ag (CH 2 QCH-O-Ag, CH 2 QCH-CHQCH-O-Al-Ag) were suggested by DFT calculations over Ag/Al 2 O 3 and Al 2 O 3 , with the simulation molecular structure model and corresponding FTIR spectrum shown in Fig. 3D-F, respectively.…”
Section: Partial Oxidation Of Oxygenated Hydrocarbons Over Ag/al 2 Omentioning
confidence: 99%
“…In recent studies, relatively durable and inexpensive alumina-supported silver catalysts (Ag/Al 2 O 3 ) have been considered to be a promising candidate for practical usage in the HC-SCR of NO x [2][3][4][5][6][7][8]. In our research into the HC-SCR of NO x over Ag/ Al 2 O 3 , we found a novel enolic surface species on Ag/ Al 2 O 3 [9] and proposed a new mechanism to explain the high-level efficiency of the SCR of NO x by ethanol over Ag/Al 2 O 3 [7,9,10], as shown in Scheme 1. The reaction starts with the formation of nitrates adsorbed on Al 2 O 3 via NO oxidation by O 2 , and enolic species and acetate adsorbed on Ag and Al 2 O 3 via the partial oxidation of C 2 H 5 OH on Ag/Al 2 O 3 [7].…”
Section: Introductionmentioning
confidence: 82%
“…So far, researchers have agreed that the -NCO species acts as the key intermediate during the SCR of NO x , and its high reactivity with NO + O 2 results in a highly efficient reduction of NO x [7, 9-11, 15, 16, 21, 28-31]. We recently proposed a novel mechanism for the SCR of NO x by C 2 H 5 OH, as shown in Scheme 1, where the surface enolic species is related to the high surface concentration of -NCO and the high efficiency of NO x reduction by C 2 H 5 OH [7,9,10]. In order to clarify the high activity of enolic species towards NO + O 2 to form -NCO, the dynamic changes of the surface intermediates on Ag/ Al 2 O 3 as a function of time have been investigated by using in situ DRIFTS measurement [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation